Unveiling The Ergo-Iconic Brand Strategy: A Qualitative Exploration of An Sem-Amos Model for Socially Responsible Investment - Andriyansah Andriyansah; Fatia Fatimah (International Journal of Applied Business and International Management, 2025)
The transition toward Socially Responsible Investment (SRI) in emerging markets requires more than regulatory ESG compliance. Despite the growing body of SRI literature, a theoretical gap persists regarding how non-financial brand heuristics influence investor capital allocation under conditions of information opacity. This study introduces the novel concept of "ergo-iconic" brand value, comprising ergonomic (functional) and iconic (symbolic) dimensions, to construct a conceptual SEM-AMOS model for SRI intention. Employing an exploratory qualitative design, we conducted in-depth interviews with 18 ESG experts and institutional investors. The findings reveal that while the Ergonomic Brand Dimension (EBD) serves as a foundational hygiene factor preventing greenwashing skepticism, the Iconic Brand Dimension (IBD) drives Sustainable Brand Equity (SBE). This research extends Signaling Theory by introducing a dual-signal heuristic and provides actionable managerial insights, emphasizing that firms must structurally reduce information asymmetry before ergo-iconic branding strategies can successfully generate sustainable capital inflows